2009
DOI: 10.1260/026309209788056357
|View full text |Cite
|
Sign up to set email alerts
|

Annoyance Related to Low Frequency Noise in Subjective Assessment of Workers

Abstract: The aim of this study was to assess annoyance related to low frequency noise (LFN) in employees of the control rooms and office-like areas. Subjects were 276 workers, aged 26–62 years, exposed to noise at A-weighted sound pressure level (SPL) of 41–66 dB. They were asked to assess noise annoyance at their workplace using a 100 point graphical scale. The subjective ratings were compared with various noise metrics and objective evaluations based on proposed LFN exposure criteria for occupational settings. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 20 publications
(22 reference statements)
2
17
0
Order By: Relevance
“…[11,29] Our recent observations from field studies comprising 276 workers confirmed that exposure to LFN in the industrial control rooms and in office-like areas at equivalent A-weighted SPLs (48−61 dB), which was well within current occupational exposure limits, could cause increased annoyance, especially in subjects recognized as more sensitive to this type of noise. [5] Our results were also in line with earlier findings that LFN was rated as more annoying than noise without (or with less prominent) low frequency content at similar dBA levels. Moreover, they suggested that the low frequency A-weighted SPL seemed to be a proper predictor for evaluation of the gravity of the annoyance experienced from LFN at workplace since, among the noise metrics, it yielded the highest correlation with subjective evaluations of LFN.…”
Section: Introductionsupporting
confidence: 93%
See 4 more Smart Citations
“…[11,29] Our recent observations from field studies comprising 276 workers confirmed that exposure to LFN in the industrial control rooms and in office-like areas at equivalent A-weighted SPLs (48−61 dB), which was well within current occupational exposure limits, could cause increased annoyance, especially in subjects recognized as more sensitive to this type of noise. [5] Our results were also in line with earlier findings that LFN was rated as more annoying than noise without (or with less prominent) low frequency content at similar dBA levels. Moreover, they suggested that the low frequency A-weighted SPL seemed to be a proper predictor for evaluation of the gravity of the annoyance experienced from LFN at workplace since, among the noise metrics, it yielded the highest correlation with subjective evaluations of LFN.…”
Section: Introductionsupporting
confidence: 93%
“…Similar results were obtained in the field study during which various evaluation methods were compared with subjective assessment of LFN at workplaces in the industrial control rooms. [5] In this study, a linear relationship between the LFN annoyance rating and almost all analyzed noise metrics was noted. But subjective assessments of LFN were significantly less correlated with HTL-based noise measures (especially L LF Tot and L LF HTL ) in older subjects (experiment II) compared with younger persons (experiment I).…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations